Avaliação de métodos de preparo de amostras para a determinação de cloro em temperos - Cajaraville, María Cecília Geisenblosen (2012)
In this study, sample preparation methods were evaluated for the determination of chlorine by ion chromatography (IC) in spice samples. The microwave-induced combustion method (MIC) was tested using certified reference materials of plants tissue. The chlorine concentration in the samples decomposed by MIC was determined by IC and inductively coupled plasma optical emission spectrometry (ICP OES). The agreement was between 100 and 105%. The sample preparation methods that were compared were: manual extraction, microwave assisted extraction in a closed system and focused microwave assisted extraction. The manual extraction method was applied to different quantities of sample from 0,25 to 1,0 g using 27 ml of water and 5 minutes of manual shaking. The results for the manual extraction method were acceptable and the recoveries obtained were between 97 and 104%. In order to evaluate the microwave assisted extraction in a closed system method different parameters were tested, such as temperature programs, sample weight and extraction solution volume, concentration and type (H2O, (NH4)2CO3, HNO3 e TMAH). For all conditions, the level of agreement between the values obtained by this method and MIC was close to 100%. On the other hand, focused microwave assisted extraction method has been tested for 1 g using different extraction solutions in different concentrations. The recovery for this method was between 88 and 102%, while the relative standard deviation values were slightly higher in comparison with those obtained with the same extraction solutions in closed systems.